Comparison of the structural properties of silicon carbide using very high frequency plasma enhanced chemical vapour deposition with magnetron sputtering techniques - Azali, Muhamad Muizzudin (2022)
In this study, the feasibility of using very high frequency (100 MHz to 200 MHz) Plasma Enhanced Chemical Vapour Deposition (VHF-PECVD) technique to deposit crystalline silicon carbide (SiC) thin films was investigated. High quality crystalline SiC film is very challenging to be produced since high temperature was always involved in the conventional deposition technique such as PECVD and Magnetron Sputtering. The VHF-PECVD technique with frequency up to 200 MHz was used to deposit the SiC thin films since only few attempts has been made using frequency higher than 150 MHz with silane (SiH4) and methane (CH4) as precursor gasses. The deposition time, Radio Frequency (RF) power and temperature were fixed at 900 seconds, 30 W and 180 oC, respectively. For comparison purpose, the well-established RF-Magnetron Sputtering technique using deposition parameters which can produce similar crystalline silicon carbide thin films was also used at RF power of about 20 W, 30 W and 150 W. Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy and Raman spectroscopy were used to determine the phase transition of films structure from amorphous to crystal. Further analysis using X-Ray Diffraction (XRD) was performed to determine the type of crystallites in the films for both deposition techniques. SiC (109) and SiC (205) were found in both techniques, but in contrast SiC (104) and SiC (103) were only formed in RF-Magnetron Sputtering and VHF-PECVD, respectively. Field Emission Scanning Electron Microscope (FESEM) and Atomic Force Microscope (AFM) were used to study the morphology of the films. Samples synthesized by VHF-PECVD were found to produce higher root-mean-square surface roughness as compared to RF-Magnetron Sputtering with a value of 12 nm and 0.70 nm, respectively. For the same 900 s deposition time, VHF-PECVD gives a better deposition rate which produced thicker films of about 276 nm as compared to 67 nm obtained with the RF-Magnetron Sputtering.